Dasar pemikiran hukum islam : taqlid X Ijtihad / Yusuf Qardhawi, Muhammad Madani, Mu - QARDHAWI, Yusuf; Madani, Muhammad; Qodri, Mu'Imuddin; Muhammad, H. Husain (Pustaka Firdaus, 1994)
iii, 98 hlm 20 cm